Fish-Based Complementary Feeding Practices Increasing Macro and Micro Nutrient Intake And Hemoglobin Levels in Anemia Toddlers - Bustami, Bustami; Suryana, Suryana; Junita, Dini; Yunianto, Andi Eka (Media Gizi Indonesia, 2023)
Iron deficiency anemia in toddlers can be prevented by introducing complementary foods alongside breastfeeding. Fish, rich in protein and iron, offers a valuable nutritional source for young children, but proper processing is crucial. This research investigated the impact of fish-based complementary food processing practices (known as MP-ASI in Indonesia) on the nutritional intake and hemoglobin levels of children under five in Tiro District, Pidie Regency. Using a quasi-experimental design, this study involved 40 toddlers from the stunting-prone area of Tiro District, Pidie Regency, along with their mothers as respondents. The toddlers, aged 12-36 months without severe illnesses, were included in the study. The intervention comprised educating and practicing complementary food processing. Before-and-after intervention comparisons showed significant improvements in energy, carbohydrate, protein, zinc, and iron intake levels. Additionally, there was a notable increase in the average hemoglobin (Hb) level, rising by 1.06 g/dl after one month of fish-based complementary food processing intervention. In summary, this intervention effectively enhanced the nutritional quality of children's intake and increased their hemoglobin levels, contributing to the prevention of iron deficiency anemia in toddlers.